Towards the Development of Intercultural Competence Skills: A Pedagogical Experience with Pre-Service Teachers - Bertha Ramos Holguín (Asociación Colombiana de Profesores de Ingles, 2013)
Although interculturality has been the focus of several studies which reveal a tendency to include an understanding of students' home culture and cultures around the world in the English language classes, few studies focus on the inclusion of an intercultural component in a class different from the English one. This article aims to share a pedagogical experience carried out in a Colombian public university in order to analyze how intercultural competence skills emerged in pre-service teachers after the implementation of an intercultural component in a research and pedagogy class. Data were gathered through field notes, students' artifacts, and group discussions. Findings revealed that pre-service teachers started to develop intercultural competence by developing skills to interpret and contextualize cultural practices and by raising awareness of contextual complexities.